A HIRARC model for safety and risk evaluation at construction site of manmade water streams and wetlands / Piradeepan Ramachandran - Piradeepan , Ramachandran (2021)
Safety at construction sites play an important role in order to protect workers from unwanted incidents which can deteriorate the company financially and its credibility. Hazards are everywhere and one should adhere to the safety regulations all the time while at workplace. This is because workers need to deal with many risky activities before and during the construction of manmade streams and wetlands, thus safety of the workers are at high risk. However, the adherence level is less impressive since few accidents are still happening during construction activities such as site clearance and excavation. Without proper supervision and enforcement, the chances of future problems will be greatly increase and this can even cause some unwanted major injuries and even death. In order to implement proper safety guidelines, all the hazards associated with the construction activities need to be identified. All these hazards need to be classified then according to the risk severity matrix. However, most of the employers are not giving much attention to these safety guidelines as they are lack in awareness and knowledge as their employees are in danger at the construction site. Risk severity matrix is useful to decide on the level of control measures based on hierarchy of control. Thus, HIRARC model is a compulsory part to be constructed before the construction activities to protect the employees from dangers.